Proteomic and cell based approaches for the study of the intestinal epithelial response to Helicobacter pylori soluble components in an ex vivo model of ulcerogenesis - Mullaney, Erica Marie (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2008)
The aim of the present study was to investigate the effects of secreted components of the gastrointestinal pathogen H. pylori on the duodenal epithelium in humans. The effects of H. pylori are not only mediated by direct interaction with the organism, but also by released bacterial elements, known as outer membrane vesicles (OMV) entering the duodenum. The primary aim of this study was to proteomically and functionally characterize H. pylori OMV. The proteome of the OMV was identified using SDS- PAGE, LC-MS/MS and Western blotting techniques. The biological activity of specific identified proteins were assessed. The putative H. pylori virulence factor vacuolating cytotoxin A (VacA) present in the OMV was found to induce vacuolation in gastric epithelial cells. The neutrophil activating protein A (NapA) also identified within the OMV was solely responsible for neutrophil migration. Furthermore, exposing T84 and AGS epithelial cells to OMV induced a dose dependent increase in lL-8 secretion. For this study T84 cells were grown in confluent monolayers, on semi permeable inserts, and apically stimulated with OMV in an in vitro model of infection. As an aim of this project was to look at the initial effects of OMV stimulation on duodenal biopsies in an ex vivo model of ulcerogenesis, this was an appropriate method by which this technique could be validated. Results from this study demonstrated that OMV, which are constantly shed from the surface of H. pylori in vivo, have a demonstrable effect on fully differentiated T84 cells. Internalisation of OMV was observed after 1 - 2 hours, changes at the protein level of the host cells after 24 hours and epithelial cell IL- 8 production. However, neither apico-basal transfer of OMV, nor any effect on barrier function or dome formation in mature monolayers of T84 cells after 24 hours were not observed. These findings support the theory that OMV play a role in promoting host responses to support persistence of H. pylori in the human gastric mucosa.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin